Production of viable cells of gdhA derivative Pasteurella multocida B:2 for use as animal vaccine - Oslan, Siti Nur Hazwani (2017)
The attenuated strain of gdhA derivative Pasteurella multocida B:2 (mutant) has demonstrated its efficacy as a live vaccine to control haemorrhagic septicaemia (HS) disease in cattle and buffaloes. However, the commercial application of this vaccine to control HS still faces some limitations such as cost effectiveness of large scale cultivation process, low cell viability and productivity, and unsuitable commercial formulation in order to sustain the cell viability of the bacterial cells in live vaccine. The main objective of this study are to develop the bioprocessing method to increase viability in terms of productivity of gdhA derivative P. multocida B:2 with minimum production cost and to develop essential formulation in powderised form with high bacterial cell survival rate for subsequent use as animal live cell vaccine. The growth medium with the addition of histidine at a concentration of 20 mM greatly improved the cell viability of P. multocida B:2 mutant in cultivation using YDB as basal medium. During batch cultivation of this mutant, ammonium accumulated in the culture greatly inhibited the growth that reduced the final cell concentration and yield. The possibility of using cation-exchange resin for in situ removal of ammonium accumulated in the culture for the improvement of the cultivation of this mutant was investigated in this study. The ability of cationexchange resins, which included Amberlite IRC-86, Amberlite IR120 H, and Dowex DRG8 H, to selectively adsorbed ammonium was first investigated. Amberlite IRC-86, which has capability on ammonium adsorption with Qmax value of 0.86 g/g as determined using sorption isotherm experiments, was chosen for in situ removal of ammonium in the culture of P. multocida B:2 mutant. In shake flask culture, the 10 g/L of Amberlite IRC-86 improved the final viable cell concentration (7.2 x 1010 cfu/mL) by about 11 time higher than that obtained in cultivation without resin (6.6 x 109 cfu/mL). In cultivation using 2 L stirred tank bioreactor with internal column containing Amberlite IRC-86, growth of the mutant was enhanced by 10% as compared to the cultivation without resin, agitated at 500 rpm. The final viable cell obtained in stirred tank bioreactor (1.05 x 1011 cfu/mL) was significantly higher than that obtained in shake flask culture. The use of trehalose as protective agent in freeze drying of P. multocida B:2 mutant cells greatly sustained the cell viability (93-95%). During storage at -30◦C and 4◦C, the freeze dried cells using trehalose was also able to maintain the viability (106-108cfu/mL) up to 6 and 12 month, respectively. The stored viable cells was still effective to be used as attenuated vaccine of P. multocida B:2.